Asymmetric conjugate addition of alkylzirconium reagents to α,β-unsaturated thioesters: access to fragrances and acyclic stereochemical arrays - Gao, Z; Fletcher, S (Royal Society of Chemistry, 2017)
Copper-catalyzed asymmetric conjugate addition of alkylzirconium species to α,β-unsaturated thioesters is reported. A variety of functionalized alkyl nucleophiles were introduced with yields around 70% and ee's over 92%. The method was applied to the straightforward syntheses of the commercially important fragrances phenoxanol (both enantiomers 97% ee), and hydroxycitronellal (98% ee). The 1,4-addition products can be converted to enantiomerically enriched linear building blocks bearing a terminal functional group. Formation of further α,β-unsaturated thioesters provides an iterative route for the stereocontrolled synthesis of functionalized acyclic arrays and we demonstrate almost complete catalyst control in the formation of additional stereocentres.